Colonic Volvulus - Savitch, Samantha L.; Harbaugh, Calista M. (Clinics in Colon and Rectal Surgery, 2023)
Colonic volvulus represents 10 to 15% of all large bowel obstructions in the United States. It most commonly occurs in the sigmoid colon or cecum. Morbidity and mortality from colonic volvulus are high. It is therefore essential to have a high level of suspicion based on presentation and expedient diagnosis and management to prevent progression to ischemia or perforation. Broad goals of management include evaluation of colon viability, relief of obstruction, and prevention of recurrence. Endoscopic and surgical approaches vary based on the site of volvulus, presence of ischemia or perforation, and patient characteristics. This review outlines the epidemiology, presentation, diagnosis, and management of colonic volvulus. A contemporary diagnostic and treatment algorithm is included.
Keywords: volvulus; colonic volvulus; sigmoid volvulus; cecal volvulus